Health effects of low dose radiation challenges of the 21st century : proceedings of the conference organized by the British Nuclear Energy Society and held in Stratford-upon-Avon, UK, on 11-14 May 1997. (British Nuclear Energy Society, 1997)
Examines our knowledge about the health effects of radiation and looks forward to developments in our understanding of the mechanisms of radiation's interaction with biological systems and the magnitude of the risks. This book also addresses the epidemiology of nuclear workforces, atomic bomb survivors and those affected by the Chernobyl accident.